Transgender college students more at risk for suicide when denied bathroom, housing rights. Issue 2 (June 2016) - Sutton, Halley
Abstract : A study published in The Journal of Homosexuality shows that transgender college students are at a significantly higher risk for suicide and suicide attempts when denied access to bathrooms and gender‐appropriate housing on campus. The study, conducted by Kristie Seelman, assistant professor of social work in the Andrew Young School of Policy Studies at Georgia State University, analyzed data from the National Transgender Discrimination Survey, including the experience of 2, 300 individuals who self‐identified as transgender during their college or university experience.